Alternative methodology for using Eureka software in the teaching-learning process - Yudeisy Cudina-Guerrero; Mayelín Figueredo-Velázquez; Maritza Palomino-Peña (Maestro y Sociedad, 2017)
In order to fulfill one of the aspects that characterized the curriculum for the training of ordinary skill in the Technical and Vocational Education which states: increase student learning in mathematics in particular, where teachers use the computer effectively as a teaching, and thus eliminate academic failure, an alternative methodology was developed to use the Eureka software, which was presented to teachers and provincial methodologists of mathematics, as well as students of Accounting, it helped to further learning students at Work with Variables. The proposal was designed to achieve a formative learning accordingly to the objectives of the program it requires Mathematics. The relevance of the alternative was assessed by consulting specialists, where they corroborated that can be educational practice.